CLAIMS FOR POSTNATAL MEDICAL SERVICES BY MIDWIVES THROUGH THE SOCIAL SECURITY ADMINISTRATOR IN KEMBANG TANJONG, PIDIE DISTRICT OF INDONESIA: AN ANALYSIS OF AKAD KAFALAH THEORY - Rayhan Fazira; Safira Mustaqilla; Nahara Eriyanti (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This study was motivated by the phenomenon of postpartum medical service claims submitted to the Social Security Agency (BPJS) in Kembang Tanjong Subdistrict, Pidie Regency, which directly affects the financial burden on independent midwives. In practice, midwives often have to cover the cost of patient treatment in advance before the claim funds are disbursed. The purpose of this study is to analyse the compatibility between the BPJS postnatal medical service claim system and the concept of kafalah in fiqh muamalah, as well as to identify the forms of risk coverage provided by midwives to patients. This study uses a qualitative method with a normative sociological approach. The results show that the BPJS claim system in the region substantially reflects the values of kafalah. Still, its implementation does not fully meet the principles of clarity (bayān) and justice (‘adl). Delays in claim payments and the layered bureaucracy within community health centres are the main factors contributing to an imbalance between the insurer’s rights and obligations and those of medical personnel. Nevertheless, the actions of midwives who continue to provide services even though they have not yet received payment reflect the value of ta‘āwun (mutual assistance) in Islam.